Anti-corrosion performance of chemically bonded phosphate ceramic coatings reinforced by nano-TiO2. (October 2018) - Liu, Yaxuan; Bian, Da; Zhao, Yongwu; Wang, Yongguang
Abstract: To promote anti-corrosion property of chemically bonded phosphate ceramic coatings (CBPCs), the nano-TiO2 is selected as the reinforcement. Differential scanning calorimetry (DSC), X-ray diffraction (XRD), Scanning electron microscope (SEM), Energy Dispersive Spectrometer (EDS) and the electrochemical analysis are carried out to clarify the role of nano-TiO2 on the improvement of anti-corrosion performance. The experiments show that with the addition of nano-TiO2, the curing temperature and the activation energy of the curing process increase, which allows longest reaction and positively drives curing reactions at elevated conversions. The enhancement of anti-corrosion performance of CBPCs reinforced by nano-TiO2 particles is based on three main mechanisms. Firstly, more bonded phase (AlPO4 ) can be formed with the addition of nano-TiO2, which can help CBPCs to get more compact microstructure. Additionally, AlPO4 particles possess the low density and good corrosion resistance, which leads to the increase in the corrosion resistance of CBPCs. Secondly, increasing content of nano-TiO2 can also strengthen the compactness of CBPCs to protect the substrates from the penetration of aggressive electrolyte and prolong electrolyte diffusion path. Thirdly, through the analysis of microstructure of CBPCs, it is found that most of the hydrophobic nano-TiO2 particles homogeneously distribute on the surface of CBPCs. Therefore, CBPCs show well hydrophobic performance, which can further improve the anti-corrosion property of themselves.